Enhanced erosion performance of cold spray co-deposited AISI316 MMCs modified by friction stir processing. (15th April 2017) - Peat, Tom; Galloway, Alexander; Toumpis, Athanasios; Steel, Russell; Zhu, Wenzhong; Iqbal, Naveed
Abstract: The present study reports on the erosion properties of a novel surface engineering process combining cold spray and friction stir processing. Tungsten carbide (WC-CoCr) and aluminium oxide (Al2 O3 ) powders were cold spray co-deposited with AISI316 using a twin powder feed system. The deposited coatings were subsequently friction stir processed to refine and redistribute the reinforcing particles and remove the coating-to-substrate interface layer, thus generating a new metal matrix composite surface. Microstructural analysis of the SprayStirred (cold sprayed then friction stirred) specimens revealed significant particle refinement and improved particle distribution over the as-deposited coatings. The erosion performance of these SprayStirred surfaces was evaluated using a flowing slurry and demonstrated an 80% decrease in volume loss over the as-received AISI316 at 30° angle of attack. For SprayStirred WC-CoCr, microhardness measurements indicated an increase of approx. 530% over the unaltered AISI316 and 100% over the cold sprayed coating. These findings highlight the considerable increase in erosion performance of the SprayStirred specimens, and thus demonstrate the benefits of this innovative surface engineering process. This outcome is attributed to dispersion strengthening, imparted by the refined tungsten carbides. Furthermore, the SprayStirred WC-CoCr coating exhibited an 85% reduction in volume loss over an HVOF sprayed WC-CoCr coating. Graphical abstract: Highlights: WC-CoCr and Al2 O3 reinforced MMC coatings were cold sprayed on AISI316 and friction stir processed. FSP homogenised the distribution of reinforcements and reduced the interparticle spacing by up to 91% in the WC-CoCr MMC. The SprayStirred WC-CoCr demonstrated a hardness increase of 500% over the AISI316. As-deposited and SprayStirred coatings were examined under slurry erosion test conditions. The SprayStirred WC-CoCr demonstrated a 77% reduction in volume loss over the cold sprayed coating at 90 O impingement.